Functional reach test: Movement strategies in diabetic subjects - Maranesi, Elvira; Ghetti, Giacomo; Rabini, Rosa Anna; Fioretti, Sandro (Gait & posture, 2014)
•Execution modalities of the functional reach (FR) test have been analysed.•Diabetics with and without neuropathy have been analysed during the FR.•Kinematic analysis is useful for subjects’ detection at risk of postural instability. Functional reach (FR) is a clinical measure, defined as the maximum distance one can reach, forward beyond arm's length, able to identify elderly subjects at risk of recurrent falls. Subjects, exhibiting the same FR can perform the motor task in different ways: a kinematic analysis of the FR, task can help to identify the motor strategy adopted. The FR test was applied to 17 diabetic non-neuropathic, (CTRL) and 37 neuropathic (DN) subjects. Motor strategies adopted were defined as: “hip” or “other” strategy; the latter included: “mixed” and “trunk rotation” strategies. Principal Component Analysis and non-parametric statistical tests were used to study the different execution modalities of the FR test. Results show that, in CTRL, the most important parameters are those related to trunk flexion in the sagittal plane. Instead, for DN, the main features are related not only to trunk flexion but also to trunk rotation in the transverse plane. Percentages of subjects who used “hip” or “other” strategies are similar for CTRL and DN subjects. However, within the “other” strategy group, the percentage of DN that used a “trunk rotation” strategy was much higher than for CTRL. Results show that individuals, although exhibiting the same reaching distance, adopt different movement strategies. Consequently it is important to evaluate the kinematic behaviour and not only the clinical measure, because the evaluation of the motor strategy might be useful in the early detection of subjects at risk of postural instability.